Prediction of astrometric microlensing events from Gaia DR2 proper motions - Klüter, Jonas; Bastian, Ulrich; Demleitner, Markus; Wambsganß, Joachim (Astronomy and astrophysics, 2018)
Astrometric gravitational microlensing is an excellent tool to determine the mass of stellar objects. Using precise astrometric measurements of the lensed position of a background source in combination with accurate predictions of the positions of the lens and the unlensed source it is possible to determine the mass of the lens with an accuracy of a few percent.Aims. Making use of the recently published Gaia Data Release 2 (DR2) catalogue, we want to predict astrometric microlensing events caused by foreground stars with high proper motion passing a background source in the coming decades.Results. We selected roughly 148 000 high-proper-motion stars from Gaia DR2 with μtot > 150 mas yr−1 as potential lenses. We then searched for background sources close to their paths. Using the astrometric parameters of Gaia DR2, we calculated the future positions of source and lens. With a nested-intervals algorithm we determined the date and separation of the closest approach. Using Gaia DR2 photometry we determined an approximate mass of the lens, which we used to calculate the expected microlensing effects.Conclusions. We predict 3914 microlensing events caused by 2875 different lenses between 2010 and 2065, with expected shifts larger than 0.1 mas between the lensed and unlensed positions of the source. Of those, 513 events are expected to happen between 2014.5 and 2026.5 and might be measured by Gaia. For 127 events we also expect a magnification between 1 mmag and 3 mag.